2010
DOI: 10.1177/159101991001600205
|View full text |Cite
|
Sign up to set email alerts
|

Bare, Bio-Active and Hydrogel-Coated Coils for Endovascular Treatment of Experimentally Induced Aneurysms

Abstract: Endovascular treatments of cerebral aneurysms with bare platinum coils have a higher rate of recurrence compared to surgical clipping. This may be related to failed vessel wall reconstruction since histological and scanning electron microscopy results following embolization failed to demonstrate neoendothelialization over the aneurysm neck. The present study tried to elucidate whether the use of modified coils resulted in a better rate of reconstructing the vessel wall over the aneurysm neck in experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Cruise et al 48 tested HydroCoils in rabbit elastase aneurysms and found high rates of long term occlusion and a twofold increase in volumetric filling of the aneurysm sac, similar to findings in human studies. These findings have been corroborated by other preclinical and clinical studies 44 49…”
Section: Device Testingsupporting
confidence: 80%
“…Cruise et al 48 tested HydroCoils in rabbit elastase aneurysms and found high rates of long term occlusion and a twofold increase in volumetric filling of the aneurysm sac, similar to findings in human studies. These findings have been corroborated by other preclinical and clinical studies 44 49…”
Section: Device Testingsupporting
confidence: 80%
“…Insertion of many coils is similar to achieving a high VER. The VER has recently been reported to be associated with aneurysmal recanalization 21 22. Many procedures and devices have been considered to increase the VER.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the shape of the coil and configuration might also affect the endothelialization process. Reinges et al 8 compared endothelialization of aneurysms embolized with bare, bioactive and hydrogel-coated coils in the rabbit model and suggested that a smooth and dense surface over the aneurysm neck is important for endothelial cells to bridge the aneurysm neck. The lack of neointimal coverage at the aneurysm neck leads to coil compaction and subsequently, recanalization of the aneurysm 22.…”
Section: Discussionmentioning
confidence: 99%